APLIKASI PUPUK N, P, K DAN KONSORSIUM MIKROBA TERHADAP PERTUMBUHAN DAN HASIL PADI INPARI ARUMBA DI TANAH ALUVIAL - Novita, Devie; Anggorowati, Dini; Palupi, Tantri (Agros Journal of Agriculture Science, 2024)
Arumba Inpari is a superior rice variety highly sought after by the community due to its red- colored rice with high nutritional content in the form of phenolic compounds, serving as antioxidants that help counteract free radicals and prevent diseases in the human body. Microbial consortium is an organic fertilizer containing superior microorganisms (Azotobacter sp., Azospirillum sp., Bacillus sp., Pseudomonas sp., and Chytopaga sp.) that enhance soil fertility more effectively than single strains. This study aims to determine the optimal dosage of N, P, K fertilizers when applied in conjunction with a microbial consortium at a concentration of 40 ml/L water. This research was conducted in the Agricultural Land of Jalan Sepakat 2 Ujung, Bansir Darat, Southeast Pontianak, starting from August to December 2023. The study utilized a Completely Randomized Design consisting of 6 treatment levels of N, P, K fertilizers (%) and microbial consortium (ml/L); m0 = (100 + 0), m1 = (100 + 40), m2 = (75+ 40), m3 = (50 + 40), m4 = (25 + 40), and m5 = (0 + 40). The variables observed in this study consist of plant height, total number of tillers, root volume, plant dry weight, panicle length, total productive tillers, number of filled grains per panicle, 1000-grain weight, and grain weight per hill. The research results indicate that reducing the dosage of N, P, and K fertilizers starting from a 25% level can decrease plant growth. However, reducing the dosage of N, P, and K from 50% to 75%, accompanied by the application of a microbial consortium, yields similar results to the application of 100% N, P, and K with respect to the crop yield variables in rice plants.